Frozen elephant trunk in total arch replacement: A systematic review and meta‐analysis of outcomes and aortic proximalization. Issue 6 (4th March 2021) - Rezaei, Yousef; Bashir, Mohamad; Mousavizadeh, Mostafa; Daliri, Mahdi; Aljadayel, Hadi Abo; Mohammed, Idhrees; Hosseini, Saeid
Abstract: Background and Aim of the Study: The frozen elephant trunk (FET) procedure became a popular entity for utilization in aortic arch aneurysm disease. However, its proper mortality and morbidities as well as the predictors of outcomes are poorly identified. This systematic review and meta‐analysis explore FET outcomes and its predictors with a focus on zone aortic proximalization. Methods: We searched PubMed/MEDLINE, EMBASE, and Scopus databases from their beginning to June 2020 to find studies reporting the outcomes of the FET procedure for the total arch replacement (TAR). Results: A total of 64 studies including 7967 patients were evaluated. The pooled estimates of cerebrovascular accidents, paraplegia, renal failure, and in‐hospital mortality were 7.104 (95% confidence interval [CI], 5.691–8.661; I 2  = 78.53%), 3.465 (95% CI, 2.852–4.136; I 2  = 15.96), 14.969 (95% CI, 11.361–18.977; I 2  = 91.26%), and 8.933 (95% CI, 7.128–10.919; I 2  = 78.51%), respectively. Stratification by the geographical locations and by the aortic pathologies led to lower heterogeneity, but not for renal failure. The distal anastomosis in Zone 2 was associated with a lower rate of renal failure compared with Zone 3 (odds ratio, 0.54; 95% CI, 0.36–0.81; p  = .003; I 2  = 0%). Conclusions: The FET procedure for TAR can be performed with acceptable mortality and morbidities among patients with complex aortic pathologies. Moreover, the distal anastomosis in Zone 2 was associated with lower renal failure compared to Zone 3.